NUKSMA DAN MUNGGUH: ESTETIKA PERTUNJUKAN WAYANG PURWA GAYA SURAKARTA - , SUNARDI ,SSN,MSN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to discuss about the elements of puppetry aesthetics, the forming process of nuksma and mungguh concept, the realisation of nuksma and mungguh in wayang performance, and nuksma and mungguh as an aesthetic orientation of wayang purwa performance of Surakarta style. Nuksma and mungguh in wayang performance are analyzed based on the aesthetic paradigm by using the concept and theory of Javanese and Indian aesthetics as an analyzing basic. The research strategy uses the approach of multi-diciplinary by borrowing the theory of rasa, the concept of garap, the theory of hermeneutics, and the concept of Javanese culture. The result of research describes that nuksma and mungguh have important roles in the aesthetics of wayang performance. Nuksma and mungguh are meant to be the accuracy and suitability in inspiring wayang performance. The elements which form the concept of nuksma and mungguh include: medium, expression, accuracy and suitability, and the dalangâs spiritual power. Nuksma and mungguh in the dalangâs soul can be reached by technical skill, garap, and expression. The realisation of nuksma and mungguh in wayang performance can be described through the accuracy and suitability of garap catur expression (the language of puppetry), sabet (wayang movements), and karawitan pakeliran that can produce the impression of rasa regu, greget, prenÃ¨s, and sedhih. Nuksma and mungguh become the basic of wayang performance inspiration and a clue for the dalangâs quality. They become the reference of wayang performance appreciation and give stimulant to the audienceâs catharsis, besides, they are related to the concept of nyawiji and kemungguhan in Javanese cultural view. The conclusion of research shows that nuksma and mungguh become aesthetic orientation in wayang purwa performance of Surakarta style.